2022
DOI: 10.1111/ceo.14083
|View full text |Cite
|
Sign up to set email alerts
|

Endocapsular artificial iris implantation for iris defects: Reducing symptoms, restoring visual function and improving cosmesis

Abstract: Background: To investigate repair of iris defects by endocapsular implantation of an artificial iris, in relation to visual outcomes, safety profile and patient satisfaction.Methods: Retrospective, consecutive case series from Greenlane tertiary teaching hospital and Eye Institute, Auckland, New Zealand. Medical records of patients implanted with an endocapsular artificial iris were reviewed and followed for minimum 3 months. Patient characteristics, surgical management, clinical outcomes and subjective respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…11 Any compromise or defect to the iris can result in a significant change to the eye's cosmetic appearance and also lead to photophobia, glare, difficulty reading and altered contrast sensitivity. 12…”
Section: Anatomy Of the Normal Irismentioning
confidence: 99%
“…11 Any compromise or defect to the iris can result in a significant change to the eye's cosmetic appearance and also lead to photophobia, glare, difficulty reading and altered contrast sensitivity. 12…”
Section: Anatomy Of the Normal Irismentioning
confidence: 99%
“…3–5 These color-changing implants placed solely for esthetic purposes in otherwise healthy eyes should not be confused with therapeutic iris prostheses, which, while less common, are still worthy of study and are the primary subject of this paper. 6–9 Inflammatory sequelae after therapeutic iris implants have been reported in some series, such as in the study by Mayer et al, while other series with the same device have not demonstrated this issue with the same frequency as Mayer's. 9,10 Early studies of UGH syndrome disclosed an association with rough, sharp, or serrated edges of intraocular implants.…”
mentioning
confidence: 97%